People of destiny : Albert Schweitzer - Richards, Kenneth G., 1926- (Chicago, Childrens Press, 1968)
1. Schweitzer, Albert
Includes Bibliography & index
Bibliography: p. 90-91.
Basic Ed. Students
Keywords: Schweitzer, Albert, -- 1875-1965 -- Juvenile literature; Schweitzer, Albert, -- 1875-1965.